Immunogenicity and safety of SARS-CoV-2 vaccine in hemodialysis patients: A systematic review and meta-analysis - Ren Peiyao; Ren Peiyao; Yu Mengjie; Shen Xiaogang; He Wenfang; Zheng Danna; Zeng Yuqun; Jin Juan; He Qiang (Frontiers Media S.A., 2022)
Rationale and objectiveCOVID-19 vaccination is the most effective way to prevent COVID-19. For chronic kidney disease patients on long-term dialysis, there is a lack of evidence on the pros and cons of COVID-19 vaccination. This study was conducted to investigate the immunogenicity and safety of COVID-19 vaccines in patients on dialysis.MethodsPubMed, MEDLINE, EMBASE, and the Cochrane Library were systemically searched for cohort, randomized controlled trials (RCTs), and cross-sectional studies. Data on immunogenicity rate, antibody titer, survival rate, new infection rate, adverse events, type of vaccine, and patient characteristics such as age, sex, dialysis vintage, immunosuppression rate, and prevalence of diabetes were extracted and analyzed using REVMAN 5.4 and Stata software. A random effects meta-analysis was used to perform the study.ResultsWe screened 191 records and included 38 studies regarding 5,628 participants. The overall immunogenicity of dialysis patients was 87% (95% CI, 84-89%). The vaccine response rate was 85.1 in hemodialysis patients (HDPs) (1,201 of 1,412) and 97.4% in healthy controls (862 of 885). The serological positivity rate was 82.9% (777 of 937) in infection-naive individuals and 98.4% (570 of 579) in patients with previous infection. The Standard Mean Difference (SMD) of antibody titers in dialysis patients with or without previous COVID-19 infection was 1.14 (95% CI, 0.68-1.61). Subgroup analysis showed that the immunosuppression rate was an influential factor affecting the immunogenicity rate (P < 0.0001). Nine studies reported safety indices, among which four local adverse events and seven system adverse events were documented.ConclusionsVaccination helped dialysis patients achieve effective humoral immunity, with an overall immune efficiency of 87.5%. Dialysis patients may experience various adverse events after vaccination; however, the incidence of malignant events is very low, and no reports of death or acute renal failure after vaccination are available, indicating that vaccine regimens may be necessary.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42022342565, identifier: CRD42022342565.